The Effect of Liquidity, Cash Flow, and Liabilities on the Profitability of Banking Companies Listed on the Indonesia Stock Exchange for the Period 2021-2024 - Mawardi; Febrianty; Rahyono (International Journal of Management, Economic and Accounting, 2026)
This study aims to examine the partial and simultaneous effects of liquidity, cash flow, and liabilities on the profitability of banking companies listed on the Indonesia Stock Exchange (IDX). The research focuses on the post-pandemic recovery period spanning from 2021 to 2024. Utilizing a quantitative approach with regression analysis, this study relies on secondary data derived from published annual financial reports. A purposive sampling method was applied to select 45 banking companies, resulting in 180 observations over the four-year period. The data were analyzed using multiple linear regression after fulfilling classical assumption tests. The findings reveal that, partially, liquidity (measured by the Loan to Deposit Ratio) has a significant positive effect on profitability (measured by Return on Investment). Conversely, cash flow (measured by Net Cash Flow) and liabilities (measured by the Debt to Equity Ratio) do not significantly dictate a positive increase in profitability. However, the simultaneous test confirms that liquidity, cash flow, and liabilities collectively exert a significant effect on the profitability of the banking companies. These results emphasize the necessity for bank management to holistically balance asset allocation, operational cash movements, and debt structures to enhance financial performance and sustain operational stability.